2005
DOI: 10.1578/am.31.4.2005.453
|View full text |Cite
|
Sign up to set email alerts
|

Whistles of Bottlenose Dolphins (<I>Tursiops truncatus</I>) in the Sado Estuary, Portugal: Characteristics, Production Rates, and Long-Term Contour Stability

Abstract: This study focuses on the whistle characteristics and production patterns of bottlenose dolphins (Tursiops truncatus) resident in the Sado Estuary, Portugal. Recordings and observations were conducted inside the estuary and in adjacent coastal waters using single hydrophones between 1987 and 2000. In the groups sampled, the mean number of whistles emitted per minute per animal was 0.28. The acoustic characteristics of a sample of 735 whistles were measured and compared with data from other Tursiops populations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 20 publications
0
35
0
Order By: Relevance
“…This hypothesis could be supported by the overall increase of the rates of all sound classes during the pre-feeding intervals. Higher rates of whistles and burst pulses have been reported in dolphins during diff erent behavioral contexts characterized by high arousal levels (Busnel and Dziedzic, 1966;Smolker et al, 1993;Norris et al, 1994;Herzing, 1996;Acevedo-Gutiérrez and Stienessen, 2004;dos Santos et al, 2005). Moreover, clicks are normally used by dolphins during inquisitive behaviors (Supin et al, 2004(Supin et al, , 2005Nachtigall and Supin, 2008).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…This hypothesis could be supported by the overall increase of the rates of all sound classes during the pre-feeding intervals. Higher rates of whistles and burst pulses have been reported in dolphins during diff erent behavioral contexts characterized by high arousal levels (Busnel and Dziedzic, 1966;Smolker et al, 1993;Norris et al, 1994;Herzing, 1996;Acevedo-Gutiérrez and Stienessen, 2004;dos Santos et al, 2005). Moreover, clicks are normally used by dolphins during inquisitive behaviors (Supin et al, 2004(Supin et al, , 2005Nachtigall and Supin, 2008).…”
Section: Discussionmentioning
confidence: 98%
“…The diversity of sounds produced by this class of animals in various contexts provides evidence that they serve a highly communicative function (Kaznadzei et al, 1976;de Waal and Tyack, 2003;Marino et al, 2007). In fact dolphins, like the complex primates (Manser et al, 2002;Seyfarth and Cheney, 2003a, b), can modify the rate of specifi c sounds in order to transmit information related to behavioral events (dos Santos et al, 2005;Gardside, 2009a, b, 2010). Even though there is no indication of the presence of referential signals in dolphins' sounds as has been reported in primates (Cheney and Seyfarth, 1982), previous studies have suggested that the variations in the acoustic characteristics (rate and type of call) of the vocalizations of dolphins might be related to emotional states and specifi c events (Tavolga, 1983;Johnson, 1993;Herzing, 1996).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Common bottlenose dolphins inhabit tropical to temperate waters globally and occur around Australia in coastal as well as offshore waters [147,272]. Bottlenose dolphins have been acousti- [501] cally recorded in QLD, Australia [284], New Zealand [285], the Eastern Tropical Pacific [151,152], Hawaii [230], California [276,286], the Gulf of Mexico [163,253,276,287], the Caribbean [288], Central America [286,289], Brazil [270,290], Uruguay [291], Argentina [276], Namibia [292], the Northwest Atlantic [163,174], the Northeast Atlantic [282,293,294], Scotland and the UK [282,295,296], Mediterranean [156,293,[297][298][299], and Portugal [300]. Many recordings have also been taken of bottlenose dolphins in captivity (e.g.…”
Section: Tursiops Truncatus-bottlenose Dolphinmentioning
confidence: 99%
“…dos Santos et al 1995;Janik 2000aJanik , 2000bCook et al 2004;Boisseau 2005;dos Santos et al 2005;Frankel et al 2014). However, the majority of research has focused on echolocation clicks and whistles (e.g.…”
Section: Introductionmentioning
confidence: 99%